The Vanity of Authenticity - DeLay, Steven (Sophia, 2021)
Traditionally, phenomenology has understood the self in light of intentionality and hence the world. However, contemporary French phenomenology—as represented here by Jean-Luc Marion—contends that this view of subjectivity is open to challenge: our mode of existence is not simply one of “being-in the-world.” I develop this claim by examining Marion’s reformulation of the reduction. Here, the phenomenon of vanity is key. I first present Husserl’s and Heidegger’s own formulations of the reduction. Following Marion, I show that the blow of vanity neutralizes both, by undercutting the respective questions to which they respond. For, in response to vanity’s own question—“What’s the use?”—neither the transcendental nor ontological reductions have a reply. Vanity consequently renders the Heideggerian distinction between authenticity and inauthenticity existentially moot. To establish this, I evaluate how existing interpretations of authenticity overlook the phenomenon of vanity. Phenomenology, I urge in conclusion, should shift its attention to the horizons opened by Marion’s erotic reduction.